Synthesis and Glycoconjugation of an Azido‐BF2–Azadipyrromethene Near‐Infrared Fluorochrome. Issue 31 (2nd October 2014) - Wu, Dan; Cheung, Shane; Daly, Robin; Burke, Helen; Scanlan, Eoin M.; O'Shea, Donal F.
Abstract: A seven‐step synthetic route to a water‐soluble azide‐functionalized BF2 –azadipyrromethene fluorochrome was developed; the fluorochrome shows λ max emission at 711 nm and a fluorescence quantum yield of 0.25. The fluorochrome can be effectively conjugated to alkyne‐substituted carbohydrates by click chemistry in water at room temperature in 20 min by using CuSO4 (20 mol‐%). The glycoconjugated fluorophores exhibit excellent near‐IR photophysical properties with little variance for different carbohydrates or from the preceding fluorochrome. The fluorescent glycoconjugates were evaluated by using confocal microscopy, and efficient cellular uptake and cytosolic localization were observed. This azido‐BF2 –azadipyrromethene fluorochrome offers the potential to be a new near‐IR imaging research tool for biology. Abstract : The synthesis of a water‐soluble azido near‐IR fluorochrome based on the BF2 –azadipyrromethene fluorophore class is described. The fluorochrome can be effectively conjugated to alkyne‐substituted carbohydrates by click chemistry in water at room temperature in 20 min. This azido‐BF2 –azadipyrromethene fluorochrome offers the potential to be a new near‐IR imaging research tool for biology.